A Comprisionol two Anesthetic Technique (mandibular block versus in filtration) in Restorative Treatment of Class I Second Mandibular Molars in 5-8 Years Children - M - Jafaerzadeh; A Forghani (Isfahan University of Medical Sciences, 2006)
Introduction: Inferior mandibular bolck anesthesia, some time causes postoperative lip and tongue biting trauma, however, an infiltration injection with a limited anesthetized area, has less complications. The aim of present study is to compare of two techniques (block and infiltration) for class I restorative treatment in primary second molars.Methods and Materials: Fourty children between 5-8 years old having bilateral calss I caries lesions on mandibular primary second molars were selected. Bite wing radiography was used to exclude proximal caries before operation. Operation was made by first using infiltration technique on one side and using block technique on the other side 72 hours later. Standard block injection technique was performed. Infiltration technique consisted of injecting half of a carpule in the bottom of vestibule between roots of the tooth and injection of 2 drops of anesthetic in mesial and distal papillae after 5 minutes. Pain was assessed using SEM (Sound, Eyes, Motor) scale by an observer who did not know which technique was used. SEM scale is a reliable and easy to administer for assessment of pain.Results: Pain during operation for both techniques, scored by SEM, was compared and there was no significant difference between block and infiltration techniques.Conclusion: Results show, according to less density of bone in buccal plate and less need to a profound anesthesia for minor restorative treatment, infiltration rechnique can be used instead of block injection in mandibular primary molars in 5-8 years children.